Nonlinear pattern of pulmonary tuberculosis among migrants at entry in Kuwait: 1997-2006 - Mohammad Hameed GHH; Akhtar Saeed (BMC, 2008)
Abstract Background There is a paucity of published data on the pattern of pulmonary tuberculosis among migrant workers entering Middle Eastern countries particularly Kuwait. The objectives of this study were to use routine health surveillance data i) to estimate the prevalence of pulmonary tuberculosis among migrant workers at entry in Kuwait and ii) to determine the occurrence of any time trends in the proportions of pulmonary tuberculosis positive workers over the study period. Methods The monthly aggregates of daily number of migrants tested and the number of pulmonary tuberculosis cases detected during routine health examinations of migrant workers from tuberculosis high-prevalence countries were used to generate the monthly series of proportions (per 100,000) of pulmonary tuberculosis cases over 120 months between January 1, 1997 and December 31, 2006 and analysed using time series methods. Results The overall prevalence (per 100,000) of documented pulmonary tuberculosis cases among screened migrants was 198 (4608/2328582). Year-specific prevalence (per 100,000) of tuberculosis cases consistently declined from 456 (95% CI: 424 - 490) in 1997 to 124 (95% CI: 110 - 140) in 2002 before showing a steady increase up to 183 (95% CI: 169-197) in 2006. The second-order polynomial regression model revealed significant (P < 0.001) initial decline, followed by a significant (P < 0.001) increasing trend thereafter in monthly proportions of tuberculosis cases among migrant workers. Conclusion The proportions of documented tuberculosis cases among migrant workers showed a significant nonlinear pattern, with an initial decline followed by a significant increasing trend towards the end of the study period. These findings underscore the need to maintain the current policy of migrants' screening for tuberculosis at entry. The public health authorities in Kuwait and perhaps other countries in the region may consider complementing the current screening protocol with interferon-γ assays to detect migrants with latent Mycobacterium tuberculosis infection. An appropriate curative or preventive chemotherapy of detected tuberculosis cases may help in further minimizing the risk of local transmission of M. tuberculosis, while contributing in global efforts to control this public health menace.